The Sense of Sounds: Brain Responses to Phonotactic Frequency, Phonological Grammar and Lexical Meaning - Silva, Susana; Vigário, Marina; Fernandez, Barbara Leone; Jerónimo, Rita; Alter, Kai; Frota, Sónia (Frontiers in Psychology, 2019)
Two outstanding questions in spoken-language comprehension concern (1) the interplay of phonological grammar (legal vs. illegal sound sequences), phonotactic frequency (high- vs. low-frequency sound sequences) and lexicality (words vs. other sound sequences) in a meaningful context, and (2) how the properties of phonological sequences determine their inclusion or exclusion from lexical-semantic processing. In the present study, we used a picture-sound priming paradigm to examine the ERP responses of adult listeners to grammatically illegal sound sequences, to grammatically legal sound sequences (pseudowords) with low- vs. high-frequency, and to real words that were either congruent or incongruent to the picture context. Results showed less negative N1-P2 responses for illegal sequences and low-frequency pseudowords (with differences in topography), but not high-frequency ones. Low-frequency pseudowords also showed an increased P3 component. However, just like illegal sequences, neither low- nor high-frequency pseudowords differed from congruent words in the N400. Thus, phonotactic frequency had an impact before, but not during lexical-semantic processing. Our results also suggest that phonological grammar, phonotactic frequency and lexicality may follow each other in this order during word processing.